Penghitungan Rasio Intensitas Ca (II) 396,8 nm dan Ca (I) 422,6 nm pada Sampel Tasbih Asli dan Imitasi menggunakan Metode Laser Induced Shock wave plasma (LISPS) - Khumaeni, Ali; Setia Budi, Wahyu; Firdausi, K. Sofjan (BERKALA FISIKA, 2006)
Spectral analysis of elemental bead samples has been done using Laser Induced Schock Wave Plasma (LISPS). This experiment is aim to distinguish between bead samples from fresh white coral and its artificial from hardwood through determination of spectral intensity of Ca(II) 396,8 nm and Ca(I) 422,6 nm. The samples are held by 10 torr and induced by NdYAG Laser 1064 nm in wavelength. Results show that the original and artificial samples can be distinguished from ratio of intensity at 1,68 : 0,80 both for white coral and its artificial from hardwood through determination of spectral intensity of Ca (II) 396,8 nm dan Ca (I) 422,6 nm respectively.